Ownership, Regulation and Socialisation: Rethinking the Principles of Democratic Media - Splichal, Slavko (Javnost-The Public, 1999)
The article examines three topics fundamental to contemporary media democratisation discourse: the principle of publicity, media agenda setting, and information subsidies. In complex democratic systems, the idea of publicity primarily refers to the media and the public sphere, where the “public use of reason” or “public discussion” can take place. The fundamental significance of the mass media for the political system is based on their role in the processes of (public) opinion formation and expression: the mass media help determine and demonstrate the limits of legitimate public discussion in society. Information subsidy limits access to information and inhibits free (political) expression by forcing the media to conform to particularistic political or commercial interests and beliefs of subsidisers. Because mass media have extremely important functions for democratic societies, they require public regulation to eventually help transform them into public services, and mass media into public service media. It is argued that media democratisation requires specific forms of regulation beyond market regulation and private subsidies in order to limit the power and control in the hands of commercial and political actors, to serve the political and economic autonomy of the media, to thwart the development of powerful coalitions between the state, capital and the media, and to encourage citizen access to the media. social management and control of the media and communication infrastructure. Forms of political and economic regulation of the media prevailing in the post-communist countries – re-nationalisation, privatisation, transnationalisation – are considered as enforcing the growth of commercial-paternalistic systems, and new forms of contents and structural regulations are suggested.